Diagnostic Value of Detecting Feline Coronavirus RNA and Spike Gene Mutations in Cerebrospinal Fluid to Confirm Feline Infectious Peritonitis - Sandra Felten; Kaspar Matiasek; Christian M. Leutenegger; Laura Sangl; Stephanie Herre; Stefanie Dörfelt; Andrea Fischer; Katrin Hartmann (Viruses, 2021)
Background: Cats with neurologic feline infectious peritonitis (FIP) are difficult to diagnose. Aim of this study was to evaluate the diagnostic value of detecting feline coronavirus (FCoV) RNA and spike (S) gene mutations in cerebrospinal fluid (CSF). Methods: The study included 30 cats with confirmed FIP (six with neurological signs) and 29 control cats (eleven with neurological signs) with other diseases resulting in similar clinical signs. CSF was tested for FCoV RNA by 7b-RT-qPCR in all cats. In RT-qPCR-positive cases, S-RT-qPCR was additionally performed to identify spike gene mutations. Results: Nine cats with FIP (9/30, 30%), but none of the control cats were positive for FCoV RNA in CSF. Sensitivity of 7b-RT-qPCR in CSF was higher for cats with neurological FIP (83.3%; 95% confidence interval (95% CI) 41.8–98.9) than for cats with non-neurological FIP (16.7%; 95% CI 6.1–36.5). Spike gene mutations were rarely detected. Conclusions: FCoV RNA was frequently present in CSF of cats with neurological FIP, but only rarely in cats with non-neurological FIP. Screening for spike gene mutations did not enhance specificity in this patient group. Larger populations of cats with neurological FIP should be explored in future studies.